Men care too: a qualitative study examining women’s perceptions of fathers’ engagement in early childhood development (ECD) during an ECD program for HIV-positive mothers in Malawi - Linda Richter; Thomas J Coates; Tijana Temelkovska; Pericles Kalande; Evelyn Udedi; Laurie Bruns; Siyenunu Mulungu; Julie Hubbard; Sundeep Gupta; Kathryn Dovel (BMJ Open)
Objectives Integrated early childhood development (ECD) and prevention of mother-to-child transmission (PMTCT) interventions rarely target fathers, a missed opportunity given existing research demonstrating that father involvement improves maternal and child outcomes. We aimed to explore mother’s perceptions of fathers’ buy-in to an integrated PMTCT-ECD programme, any impact the programme had on couple dynamics, and perceived barriers to fathers’ involvement in ECD activities.Design Qualitative study using individual in-depth interviews with mothers participating in a PMTCT–ECD programme. Interviews assessed mothers’ perceptions of father buy-in and engagement in the programme and ECD activities. Data were coded using inductive and deductive strategies and analysed using constant comparison methods in Atlas.ti V.1.6.Setting Four health facilities in Malawi where PMTCT services were provided.Participants Study participants were mothers infected with HIV who were enrolled in the PMTCT–ECD programme for >6 months.Interventions The PMTCT–ECD intervention provided ECD education and counselling sessions during routine PMTCT visits for mothers infected with HIV and their infants (infant age 1.5–24 months). The intervention did not target fathers, but mothers were encouraged to share information with them.Results Interviews were conducted with 29 mothers. Almost all mothers discussed the PMTCT–ECD intervention with male partners. Most mothers reported that fathers viewed ECD as valuable and practised ECD activities at home. Several reported improved partner relationships and increased communication due to the intervention. However, most mothers believed fathers would not attend the PMTCT–ECD intervention due to concerns regarding HIV-related stigma at PMTCT clinics, time required to attend and perceptions that the intervention was intended for women.Conclusions Fathers were interested in an integrated PMTCT–ECD programme and actively practised ECD activities at home, but felt uncomfortable visiting PMTCT clinics. Interventions should consider direct community outreach or implementing ECD programmes at facility entry points where men frequent, such as outpatient departments.